Factor Comparison for Participation in Training Program: The View of Training Officer and Academic Staff at Public University Malaysia - Syah Mokhtar, Ikram; Hazana Abdullah, Nor; Mahmood Salman, Peshraw; Anwer Ismael, Darbaz; Othman, Bestoon (International Journal of Psychosocial Rehabilitation, 2019)
Training and development have been seen as an important tool for organizational needs. In fact, the quality of employees and continuous improvement in skills and productivity through training are now widely recognized as important factors in ensuring long-term success in an organization. Staff participation in training programs is essential in achieving the goals and needs of a training program. In line with this, the study aims to continue to compare factors affecting participation in training programs based on feedback from training officers and academic staff at Public University Malaysia. The study uses qualitative methods where seven (7) training officers and 28 (twenty-eight) academic staff of the Public University in Malaysia have been interviewed. The data obtained was analysed using Nvivo10 application. Based on the analysis, training staff argued that individual factors are the main factors affecting academic staff in training programs. While the academic staff of the Public University in Malaysia suggested that work factors are the main factors that influence them to attend training programs. It is hoped that the study findings can be used by the parties to help increasing participation rate in training programs.